2019
DOI: 10.1177/1120700019881413
|View full text |Cite
|
Sign up to set email alerts
|

Anterior versus posterior approach total hip arthroplasty: patient-reported and functional outcomes in the early postoperative period

Abstract: Purpose: Direct anterior approach total hip arthroplasty (DA THA) has been reported to improve early outcomes compared to posterior approach THA up to 6 weeks postoperatively. Limited weekly outcomes data are available prior to 6 weeks. We evaluate outcomes including when patients first drive a car, leave home, and discontinue their assist device. Methods: Patients undergoing THA for primary osteoarthritis were prospectively enrolled. Outcomes data were collected preoperatively and postoperatively at weekly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 20 publications
0
26
0
2
Order By: Relevance
“…Some studies show that compared with the PA, the DAA leads to less blood loss, low transfusion rates, shorter surgery times, a shorter length of hospital stay (LOS), low postoperative complication rates and better functional recovery [10][11][12][13][14][15][16][17]. Other studies have shown that DAA is associated with higher postoperative complication rates than is PA [18,19], especially regarding neuropraxia in the lateral cutaneous nerve of the thigh [18,20].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies show that compared with the PA, the DAA leads to less blood loss, low transfusion rates, shorter surgery times, a shorter length of hospital stay (LOS), low postoperative complication rates and better functional recovery [10][11][12][13][14][15][16][17]. Other studies have shown that DAA is associated with higher postoperative complication rates than is PA [18,19], especially regarding neuropraxia in the lateral cutaneous nerve of the thigh [18,20].…”
Section: Introductionmentioning
confidence: 99%
“…However, more recent studies have begun to use PROMIS instruments in assessment of outcomes related to surgical intervention for different hip pathologies. Clinical studies on outcomes after THA have used PROMIS scores for assessment of both functional outcomes and pain improvement postoperatively . PROMIS instruments have been used in clinical trials assessing baseline disability and functional performance in patients with femoroacetabular impingement (FAI) .…”
Section: Patient‐reported Outcomes Measurement Information Systemmentioning
confidence: 99%
“…Further evaluation of the psychometric properties of PROMIS instruments, specifically for hip pathology, would be beneficial; however, PROMIS instruments have been used in several clinical trials involving THA, FAI, and hip dysplasia . Investigators should take note of the previously reported high floor effects in THA populations .…”
Section: Patient‐reported Outcomes Measurement Information Systemmentioning
confidence: 99%
“…On one hand, the direct anterior approach (DAA) is seen as a kind of true minimally invasive approach because of less muscle damage, which enters the operation area of the hip joint by muscle gap [7,8] .On the other hand, the conventional posterior approach (PA) is the most frequently used surgical approach for THA [9] . Some studies show DAA is inclined to less blood loss, low transfusion rates, shorter surgery times, shorter length of hospital stay (LOS), low postoperative complication rates and better functional recovery [10][11][12][13][14][15][16][17] . Some other studies find higher postoperative complication rates in the DAA group compared with PA group [18,19] , especially the lateral cutaneous nerve of thigh neuropraxia [18,20] .…”
Section: Introductionmentioning
confidence: 99%